EFL Students’ Attitude toward Learning English by Using Collaborative Learning - Afi Normawati; Allvian Ika Fiki Susanto; Aziza Restu Febrianto; Farikah Farikah (Acitya: Journal of Teaching and Education, 2023)
The ability to use English to communicate is strongly needed in this era; therefore, learning English has now become a requirement for all students worldwide. Many strategies have been used in the process of learning English; one of them is by implementing collaborative learning. The purpose of this research is to identify EFL students’ attitudes to learning English by using collaborative learning. This study obtained the data from a questionnaire with a 5-point Likert scale and open-ended questions to determine students' attitudes when participating in collaborative learning activities. The results show that the students have positive attitudes toward learning English by using collaborative learning. The students believe that collaborative learning can improve comprehension, increase motivation, cooperation, and confidence, as well as communication skill. Even though they face some challenges such as different views among students and longer time in completing tasks, students can accomplish tasks better than when working alone. Thus, it is suggested that the lecturers build strategies to improve the implementation of collaborative learning in the EFL learning activities to ensure that the learning is organised more effectively.